Theoretische Analyse der Strategienwahl unter der Zwei- und Drei-Punkte-Regel im Fußball - Hannah Geyer (Westfälische Wilhelms-Universität Münster, Institut für Ökonomische Bildung (IÖB), 2008)
The paper theoretically analyses the effect of the introduction of the three-point-rule on the strategies in a soccer match. Therefore the expectation values for the goal difference at the end of the game under different strategies both for matches between equally strong teams and (more realistically) for matches between teams with varying quality levels are simulated. It can be shown that the rule change in tied games between equally strong teams leads to a more offensive manner of play, while in matches between teams with varying quality levels the weaker team plays in any case more offensive, while the stronger team only plays more offensive if the gap between the quality of the teams is not too big. If one team leads in matches with homogenous teams the leading team now changes later from an offensive manner of play to a defensive manner. In matches with heterogeneous teams with the better team in lead this team changes its manner of play earlier from offense to defence and if the weaker team leads it changes its strategy earlier.
Keywords: C72; L83; 330; Fußballsport; Strategie; Betriebswirtschaftliches Ziel; Spieltheorie; Theorie; Deutschland